2023
DOI: 10.1159/000529314
|View full text |Cite
|
Sign up to set email alerts
|

Bacillary Layer Detachment in Diabetic Retinopathy: A Case Report

Abstract: To our knowledge, this is the first report to describe bacillary layer detachment (BLD) in a patient with diabetic retinopathy treated with anti-vascular endothelial growth factor. We present the case of a 55-year-old diabetic female who was referred to our hospital complaining of decreased vision in her left eye for 2 weeks. Fundus examination of both eyes was compatible with diabetic retinopathy. Spectral-domain optical coherence tomography of the left eye showed a large dome-shaped cystic space with margina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…In a recent case report by Amini et al also revealed a 55-year-old female with diabetic retinopathy was treated with a single dose of anti-VEGF and resulted in increased visual acuity and complete remission of BALAD. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent case report by Amini et al also revealed a 55-year-old female with diabetic retinopathy was treated with a single dose of anti-VEGF and resulted in increased visual acuity and complete remission of BALAD. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…But we postulate that the improvement in visual acuity induced by regression of SRF markedly outweighs the decrease caused by BALAD and the formation of EZ/IZ disruption following BALAD resolution.Moreover, Amini et al documented progressive restoration of the EZ during long-term follow-up, which may also explain the improvement in visual function after BALAD remission. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation